The Impact of Experiential Learning on Climate Change Awareness in Sustainability Education: A Systematic Review - Pratama, Ariyoga (SEAQIS Journal of Science Education, 2025)
This systematic review evaluates the effectiveness of experiential learning methods, including hands-on activities, in enhancing climate change awareness among high school students within sustainability education. By comparing these approaches to traditional lecture-based instruction, the review identifies key facilitators and barriers to their implementation in educational settings. The study follows the PICO framework to define the Population, Intervention, Comparison, and Outcome, and uses the PROMPT mnemonic to assess the Presentation, Relevance, Objectivity, Methodology, Provenance, and Timeliness of the included studies. From 579 initial records, 25 studies met the inclusion criteria, spanning a range of geographic regions and intervention types. The findings indicate that experiential learning significantly improves students' climate change awareness by fostering engagement, real-world application, and collaborative learning. However, challenges such as limited resources, insufficient teacher training, and curricular constraints hinder broader adoption. This review highlights the value of integrating experiential learning into high school sustainability curricula and calls for further research on long-term impacts, culturally responsive practices, and the development of effective assessment tools and teacher support systems.